Penyelesaian Sengketa Perdata Antara Kontraktor dan Sub Kontraktor dalam Proyek Konstruksi (PT. Hsing Loong Indonesia dan PT. Alfa Mandiri) - Wicaksono, Ario; Sami'an, Sami'an; Hardjomuljadi, Sarwono (Syntax Literate, 2025)
This study examines the civil dispute resolution process between contractors and subcontractors in a construction project, based on a case study of PT. Alfa Mandiri versus PT. Hsing Loong Indonesia (Decision Number 124/Pdt.G/2020/PN.JKT.SEL). The dispute arose from a subcontract agreement drawn up solely in English and not in Indonesian, as required by Law Number 24 of 2009 concerning the National Flag, Language, Emblem, and Anthem. Furthermore, differing interpretations of the contract's contents and disharmony in project implementation led to a lawsuit filed with the South Jakarta District Court. This study aims to analyze the parties' responsibilities, the legal basis for contract cancellation, and the civil dispute resolution mechanism in construction projects in Indonesia.